WALK: THE BENEFITS OF PHYSICAL ACTIVITY (Fiep Bulletin - online, 2012)
Due to growing demand for better quality of life, people seek a solution in physical activity to reduce risk factors. This research aimed to examine how this practice is performed on the walk (systematic) in one of the edges of Macedonia as a starting point with the interest of guidance from a professional physical education, even by the fact that these individuals do not know the possible problems caused by a practice of improperly. MethodologyThis is a survey along the coast of Macedonia, which aimed to verify if the practitioners of this activity is receiving or not receiving adequate guidance for this type of practice. The research is characterized as a field study, quantitative descriptive. A questionnaire was given to 50 people. The results show that in general a small part of respondents, receive guidance from a professional physical education. Thereby making evident the need for monitoring of a qualified professional. We conclude that most people who walk on the edge of the city of Maceio, according to the Americam College of Sports Medicine, 2003 should start to practice before the walk start a pre-participation screening so that this way she can establish an intensity activity moderate thus obtaining better results more safely.
Keywords: Quality of life and health walk